Semantic knowledge representation for information retrieval - Gödert, Winfried; Hubrich, Jessica; Nagelschmidt, Matthias (Walter de Gruyter GmbH, 2014)
This book covers the basics of semantic web technologies and indexing languages, and describes their contribution to improve languages as a tool for subject queries and knowledge exploration. The book is relevant to information scientists, knowledge workers and indexers. It provides a suitable combination of theoretical foundations and practical applications.